A review of chalcogenide-based perovskites as the next novel materials: Solar cell and optoelectronic applications, catalysis and future perspectives - George G. Njema; Joshua K. Kibet (Next Nanotechnology)
The increasing demand for renewable energy has stimulated significant advancements in the photovoltaic technology (PV), with perovskite solar cells (PSCs) emerging as leading alternatives because of their impressive efficiency and versatile characteristics. Nevertheless, conventional lead-based PSCs face critical challenges such as environmental instability, lead toxicity, and limited durability, which hinder their broader commercial applications. Chalcogenide-based perovskites, on the other hand have been advanced as promising options, offering improved stability, less toxic compositions, and the potential for more cost-effective, scalable production. This review thoroughly examines the progress made in chalcogenide perovskite research, highlighting their tunable bandgaps for diverse applications, superior charge transport properties, and resilience against advanced weathering conditions such as moisture, oxygen, and UV light. The graphene-like characteristics of certain chalcogenide perovskites, which contribute to their high charge mobility and flexibility, make them strong candidates for the next-generation PV technologies. Furthermore, this work explores the expanding potential for indoor applications of these materials, including their integration into flexible indoor PSCs and other optoelectronic devices designed for controlled environments. Also, various synthesis and optimization strategies, such as advanced deposition techniques, precise doping methods, and innovative interface and additive engineering are presented, aimed at enhancing the PV performance of these materials. Accordingly, this review bridges the gap between fundamental research and practical applications, outlining a strategic direction for developing chalcogenide-based PSCs and optoelectronic devices that meet the global energy demand while advancing sustainability and environmental safety.